Low-carbon energy transition from the lens of feminist theories - Dalia Štreimikienė (Contemporary Economics, 2023)
Climate change mitigation pledges require decarbonization of the economy and the creation of a carbon-neutral society. Men and women contribute differently to climate change and have different roles in low-carbon energy transition. Gender roles influence career choices, abilities to invest in low-carbon solutions, power of decision-making, dissimilar mobility and energy consumption demands, and different values and consumption profiles, shaping the individual carbon footprint and behavior. A feminist methodology in gender- just low-carbon energy transformation goes beyond the introduction of certain gender-equal redistribution measures and aims to deal with the core roots of the different unequal practices in all fields of society life. It seeks to rebalance prevailing power arrangements, centering the most marginalized individuals and groups. There are various frameworks developed for the analysis of linkages between climate change and women following the feminist theory, like gender impact assessment (GIA); gender equality training (GET) model, and so on. The paper applies the feminist theory approach to the analysis of low-carbon energy transitions. The main purpose of using a feminist lens in this study is to enable the discovery of how people interact within energy systems and to offer solutions to confront and eradicate oppressive structures for just low-carbon energy transition in the EU.
Keywords: H30; P18; Q20; Q30; 330; ow-carbon energy transition; climate change mitigation; feminist theory; gender equality